Professional Competence of Islamic Religious Education Teachers to Improve Students' Mastery of Learning Materials - Najamuddin Petta Solong; Ahmad Fakhrurrazi Mohammed Zabidi; Ni'ma M. Alhabsyi (Indonesian Journal of Islamic Education Studies (IJIES), 2022)
This study aims to analyze Islamic religious education (IRE) teachers' professional competence to improve students' mastery of learning materials after the Covid-19 pandemic in one of the madrasahs at the junior-high-school level in Gorontalo City. The research method used is Venetian qualitative research. Data collection techniques were obtained through observation, interviews, and documentation. The data validity uses triangulation, and the data analysis is descriptive. The research results showed five categories related to the Islamic religious education teachers' professional competence to ensure students' mastery of learning material: different abilities in adjusting face-to-face learning, diversity of teacher professional competencies, the lack of teachers' reflective actions, the ease of learning being uneven among students, and insignificant change in student learning outcomes.